(untitled) (Research, Society and Development, 2020)
Objective: To identify the social and individual vulnerability to intestinal parasitic infection in the coastal communities of São Ciríaco, Campus Urucurituba and Campus Aramanaí located in the municipality of Santarém in the state of Pará. Methodology: A form was applied to the participants containing questions about their hygienic- Sanitary. There was a distribution of sterile parasitological collector and later the collection, the fecal biological material was identified and sent for laboratory analysis. Results: The sample consisted of 111 participants, aged 1 to 70 years. The profile of the participants attended showed a predominance of females, 78 (70.27%). Regarding the occurrence of diarrhea in the family, 86 (77.48%) said they had had diarrheal episodes. The parasites that predominated in the analyzed samples were Entamoeba coli (44.44%) and Entamoeba hystolytic (22.22%). Conclusion: It can be said that the investigated communities are in a situation of vulnerability, requiring special attention from health professionals in order to enable residents, both the appropriate treatment and health education to learn about sanitary measures to fight parasites.